Kemelimpahan anggang-anggang Ptilomera dromas Breddin (Hemiptera: Gerridae) di Sungai Ciliwung dalam kaitannya dengan kualitas air - Budi Setiawan; Tri Atmowidi; Sulistijorini Sulistijorini (Jurnal Entomologi Indonesia, 2022)
Water-strider Ptilomera dromas Breddin (Gerridae: Hemiptera) is an aquatic insect that is commonly found in various waters, such as rivers, ponds, and lakes. The purpose of this research was to study the abundance of P. dromas in Ciliwung river in relation to its water quality. The abundance of P. dromas was surveyed at five stations, i.e. Cilember, Cijulang, Gadog, Katulampa, and Sempur stations. Environmental parameters measured were water temperature, air temperature, pH, water flow, biological oxygen demand (BOD), dissolved oxygen (DO), free CO2 level, nitrogen total, water hardness, and total suspended solid (TSS). The relationship of P. dromas abundance with environment parameters was analyzed by using general linear model (GLM). Results showed that the highest abundance of P. dromas was found in Gadog station, followed by Cilember, Katulampa, and Cijulang stations. The population of P. dromas was not found in Sempur station, which might be related to the presence of Katulampa weir that acts as physical barrier and due to high BOD and TSS values. Based on GLM analysis, water hardness and pH were correlated positively with abundance of P. dromas. The existence of P. dromas in the upstream stations is linked to the high water quality and low pollution of waters.